Military Diplomacy as A Soft Power Strategy: Nepal-India Relations since 2015 - Limbu, Prem Prasad (Unity Journal, 2022)
The military diplomacy has increasingly occupied a wider space in Nepal-India bilateral ties. It has been an effective soft power instrument to convey the message of alive relationship, to bond the ties stronger and to revive the strained relationships. Today, it has got a central place of political as well as public concern. Such glorious history of military diplomacy begins after the challenging official visit of Chief of Army Staff (CoAS) of Nepal to India in 2016 and successful role to revive the severely ruined Nepal-India relationships by ending the unofficial blockade of India imposed to Nepal. Later, it has been recertified considering the Indian Army (IA) Chief’s visit to Nepal in 2020 as an icebreaker visit to reset soured bilateral relationship between two immediate neighbors developed after a bitter boarder row dispute in Kalapani-Lipulekh-Limpiyadhura area. These instances produce a new sequence, value and significance of military diplomacy in contemporary Nepal-India ties and raise a question. Why and how the military diplomacy as a soft power strategy is a constructive and useful in diplomatic relation of two democratic states Nepal and India in the twenty-first century. This study answers this question through the secondary data interpretation observed in practices of military diplomacy employed between two states and analyses of them by linking to the concept of soft power thematically in qualitative style. For this, Indian unofficial blockade imposed upon Nepal and Kalapani-Lipulekh-Limpiyadhura territorial border dispute started since 2019 are two major issues of study. The study finds, the issue of economic blockade and boarder row produced during 2015-2021 are the main factors which shifted the Nepal-India ties into a new paradigm, expanded the role of military diplomacy in new heights and developed a new public trust upon the military performance as a soft power in diplomatic realm. To present this idea, the writing contains contextual and conceptual operations of military diplomacy, soft-power and realism in first part, detail account of practice of military diplomacy in middle part, and conclusion in last part.